2020
DOI: 10.1186/s12933-020-01001-y
|View full text |Cite
|
Sign up to set email alerts
|

The pro-inflammatory marker soluble suppression of tumorigenicity-2 (ST2) is reduced especially in diabetic morbidly obese patients undergoing bariatric surgery

Abstract: Background: High soluble suppression of tumorigenicity-2 (sST2) is a marker of poor prognosis in chronic inflammatory conditions. ST2 and its ligand interleukin (IL)-33 are elevated in adipose tissue of obese individuals. We aimed to evaluate circulating sST2 and IL-33 as possible markers of metabolic benefit in morbidly overweight patients after Roux-en-Y gastric bypass (RYGB) bariatric surgery.Methods: sST2, IL-33, high sensitive IL-6, high sensitive C-reactive protein (hsCRP), leptin, cholesterol metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In contrast to the modest weight loss achieved in our study in either arm, a drastic body weight reduction associated with bariatric surgery led to a significant reduction in sST2 especially in diabetic patients [ 31 ]. This is probably related to the profound cardiometabolic reprogramming induced by bariatric surgery [ 32 ].…”
Section: Discussionmentioning
confidence: 56%
“…In contrast to the modest weight loss achieved in our study in either arm, a drastic body weight reduction associated with bariatric surgery led to a significant reduction in sST2 especially in diabetic patients [ 31 ]. This is probably related to the profound cardiometabolic reprogramming induced by bariatric surgery [ 32 ].…”
Section: Discussionmentioning
confidence: 56%
“…Bariatric surgery in severely obese diabetes patients improves metabolic status, and circulating sST2 levels decrease with improvements in liver function and lipid metabolism markers 32 . In line with these findings, we found that sST2 is correlated with DM and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 diabetes patients with normal blood glucose tolerance, circulating sST2 levels were significantly higher and were significantly associated with fasting blood glucose and HbA1c ( 31 ). Bariatric surgery in severely obese diabetes patients improves metabolic status, and circulating sST2 levels decrease with improvements in liver function and lipid metabolism markers ( 32 ). In line with these findings, we found that sST2 is correlated with DM and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 serves as an important local link between tissue injury or metabolic disturbances and a physiological response to limiting and repairing tissue damage [ 45 ]. It has been shown that circulating sST2 is associated with markers of liver function and lipid metabolism in severely obese patients and that a reduction in sST2 occurs after successful bariatric surgery, most prominently in patients with diabetes [ 46 ]. IL-33 and sST2 are abundantly expressed in adipose tissues, and IL-33 levels are correlated with high BMI, suggesting an association of IL-33 with obesity and diabetes [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%